Workload Migration to Cloud: A Comprehensive Review and Analysis - Mathunni, Binoy (Digital Repository of Theses - SSBM Geneva, 2025)
Cloud computing has become a game-changing technology for enterprises with its unparalleled scalability, agility, and cost-effectiveness. Cloud migration has emerged as a strategic necessity for enterprises looking to take advantage of cloud computing's advantages as they work to maximize those benefits. In line with this significance, it is necessary to have a thorough understanding of this concept, including these advantages and disadvantages as well as the strategies or factors that has to be considered to ensure an efficient migration that realizes the full benefits for enterprises. Therefore, the purpose of this critical study is to comprehend the potential and difficulties related to moving workloads to the cloud as well as the most effective techniques for an efficient transition for businesses. As part of its methodology, the study evaluated prior research papers using a qualitative, systematic review approach in order to address the research questions. Content analysis was used to examine the data that was taken out of the chosen articles. The study's findings show that because the cloud computing ecosystem is always changing, both small and large enterprises have embraced cloud migration strategies. This move is beneficial for a number of reasons, including cost-effectiveness, adaptability, and agility. However, moving to the cloud is not without its difficulties, and managers and company executives in charge of the process should be aware that there are significant risks associated. Notably, while navigating these obstacles, the conversation has revealed important factors that affect how well workloads are moved to the cloud. The results highlight how crucial careful risk assessment, strategic planning, and the incorporation of best practices are to a successful move to enable businesses to maximize their cloud transition initiatives. Future research may focus on dwelling on the challenges of workload migration and providing solutions that companies can adopt to counter the challenges using methodologies such as interviews or questionnaires to get information from cloud providers and companies.